القانون الدولي الجزائي وأهم التطبيقات العملية - عزوز, عبد القادر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعتبر القانون الدولي الجزائي أهم فروع القانون الدولي العام, وقد جاء نتيجة بروز عدد من الأفعال التي تتجاوز في خطورتها وجسامتها ما تصل إليه الجرائم الجنائية العادية, وبالتالي عند العودة إلى تطور القانون الدولي الجزائي, لاحظنا أنه قد تطور الجانب الموضوعي أكثر من الجانب الإجرائي, والذي مرَّ بمراحل عديدة إلى أن وصلنا إلى القضاء الجزائي الدولي الدائم ( المحكمة الجنائية الدولية ), ورغم أن نظام روما الأساسي الذي لعب دوراً في تقنين مبادئ القانون الدولي الجزائي, كان يعتمد بشكل أساسي على القانون العرفي كأحد أهم مصادره, وقد واجه عمل المحكمة الجنائية الدولية منذ نشأتها إلى الآن عدداً من التحديات تناولنا أبرزها : تحدي السيادة الوطنية, تحدي هيمنة مجلس الأمن, تحدي رفض الولايات المتحدة الأمريكية لنشأة وعمل المحكمة وتناول البحث تحليل أهم وأبرز هذه التحديات وتأثيرها, وإمكانية تأسيس بيئة قانونية لتنفيذ العدالة الدولية . International criminal law is considered to be the most important branch of international public law. It has been the result of the emergence of a number of acts that go beyond the gravity and gravity of ordinary criminal offenses. Consequently, when we return to the development of international criminal law, we have noticed that the substantive aspect has evolved more than the procedural aspect, It passed through several stages until we reached the permanent International Criminal Court (ICC). Although the Rome Statute, which played a role in codifying the principles of international criminal law, relied mainly on customary law as one of its most important sources, Since its inception to date a number of challenges, the most prominent of which are: The challenge of national sovereignty, the challenge of the hegemony of the Security Council, the challenge of the United States rejection of the establishment and functioning of the Court The study examined the most important and prominent of these challenges and their impact, and the possibility of establishing a legal environment for the implementation of international justice.